The Difference of Lymphocyte, hs-CRP, and Electroencephalogram with and without Simvastatin in Acute Ischemic Stroke - Chairil Amin Batubara; Aldy Safruddin Rambe; Nindia Sugih Arto (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2020)
Mortality and morbidity due to stroke rank the highest in Indonesia (15.4%), and most types of stroke are ischemic (87%). Inflammation has a role in the pathophysiology of both ischemic stroke and also inhibits acute symptomatic epileptic seizures (3-6%) in the first 7 days after stroke. Statins have been used for the treatment of dyslipidemia in stroke patients. Some studies showed that statins reduced the inflammatory response after a stroke and prevented the recovery of epileptic seizures. This study aimed to determine the differences in lymphocytes, hs-CRP, Electroencephalogram (EEG) with and without Simvastatin in acute ischemic stroke. This research was an experimental study with a double-blind, randomized control trial design consisting of two groups, a group given Simvastatin 20 mg/day, and a group given a placebo for seven days. The difference in lymphocytes, hs-CRP, EEG, and epileptic seizures between the two groups were then analyzed. The sample was 26 people, consisting of 17 (65.4%) males and 9 (34.6%) females with an average age of 59±5.8 years. Chi-Square and Fisher's test showed a significant difference in hs-CRP (p=0.005) and epileptic seizures (p=0.015), but no significant difference in lymphocytes (p=0.336) and EEG (p=0.42) between groups given Simvastatin 20 mg/day and those given placebo. There was a significant difference in hs-CRP and epileptic seizures, but no significant difference in lymphocyte count and EEG between the two groups with and without Simvastatin administration.